The Structure of Professional and Pedagogical Competences Development of Students as an Example of a Short-Term Academic Pen (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Clarification of the concept of short-term pencil drawing is one of the main goals of this study, as it allows systematization of important materials collected by different approaches and schools.